Longitudinal changes in home food availability across the first 3 years of life and associations with family context predictors - Fiese, Barbara H.; Barton, Jennifer M.; Sahin, Esra (Frontiers in Nutrition, 2023)
Background: There is limited research tracking changes in home food availability during the first three years of life and whether the family context influences these changes.Objective: This study examined changes in and predictors of home food availability across the first three years of life.Design: This study utilized longitudinal data from the STRONG Kids2 birth cohort from the target child at 6 weeks to 36 months postpartum.Participants: Mothers of 468 children were surveyed at 6 weeks, 3, 12, 24, and 36 months postpartum.Methods: Home observations were completed by trained research assistants to complete the presence of foods in the home. The primary outcomes were the availability of ten food groups and scores from the Home Food Inventory (HFI), including dairy (regular fat), dairy (reduced fat), processed meats, other meats and non-dairy protein, savory snacks, vegetables, vegetables (no potatoes), and three obesogenic scores. Repeated measures ANOVA were used to examine changes in the HFI food groups and obesogenic scores over time. Multilevel regressions were conducted to examine whether the presence of an older sibling, entry into childcare, and mother's return to full-time work were associated with the HFI.Results: Significant changes were detected for dairy (regular fat), other meats and non-dairy protein, savory snacks, vegetables, vegetables (no potatoes), and all obesogenic scores across time. A linear trend occurred for most HFI groups, however, the third obesogenic score (without milk and cheese) was highest at 3 months, declined at 12 months, and then slowly increased from Home Food Availability 2 12 to 36 months years. The presence of an older sibling was a consistent predictor of the HFI groups over time. Entry into childcare was only associated with the availability of processed meats.The availability of food types shift as children age and their dietary needs alter. It is important to consider the whole family context such as the presence of older siblings whose dietary needs may differ from younger children. Future efforts are warranted to consider changes in food availability among diverse samples and different family structures.